Soil C/N ratio governs bacterial community assembly along an arid mountain elevational gradient - Zhang, Yongguang; Li, Chaonan; Zeng, Fanjiang; Zhang, Bo; Zhang, Zhihao; Li, Chenhong; Jiang, Hongchen (Frontiers in Microbiology, 2026)
The mechanisms governing soil bacterial community assembly along elevational gradients in cold-arid mountains remain poorly understood, despite their critical role in these fragile ecosystems. This study investigates these mechanisms along a pronounced climatic and vegetational gradient (1,707–3,548 m) on the northern slope of the Central Kunlun Mountains. The results show that bacterial α-diversity increased with elevation, while β-diversity exhibited a hump-shaped pattern. Mean annual precipitation (MAP) and vegetation cover were the primary drivers of these patterns, exerting stronger influences than soil pH. This suggests that arid-adapted bacteria possess unique environmental tolerances. Notably, after accounting for multicollinearity among environmental factors, the soil organic carbon-to-nitrogen (C/N) ratio emerged as the dominant factor shaping community assembly. At higher elevations (≥2,746 m), we observed increased phylogenetic clustering, linked to vegetation-driven deterministic selection via stable organic matter inputs and root exudates. However, stochastic processes still dominated the overall assembly. These findings highlight a pivotal mechanism wherein vegetation mediates bacterial community assembly primarily through modulating the soil C/N ratio in arid mountains. This study refines microbial biogeographic models by emphasizing the interplay between vegetation and soil stoichiometry under environmental stress, providing crucial insights for predicting ecosystem responses to climate change.